Pengaruh Video Pembelajaran Terhadap Hasil Belajar Siswa SMP IT Yaa Bunayya Makassar Pada Pelajaran Matematika - Monoarfa, Merrisa; Zakiyah Shalehah; Pattaufi (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
Education includes learning and teaching activities. Communication media in the learning process is often referred to as learning media. The main function of learning media is as a means to achieve learning objectives. The more effective the learning media used, the more effective the learning process will be. The purpose of this study is to determine the effect of using learning videos on student learning outcomes. This research uses a quantitative approach with the type of pre-experimental research. Data collection techniques in the form of tests, interviews, observation, and documentation. Data analysis techniques using descriptive statistical analysis. This research uses a quantitative approach with the type of pre-experimental research. Data collection techniques in the form of tests, interviews, observation, and documentation. Data analysis techniques using descriptive statistical analysis. The results showed that the learning process lasted for four meetings and was observed using the learning process implementation sheet using audio-visual media (learning video), the results obtained showed the progress of improvement in each meeting and were categorized as effective.